2017
DOI: 10.1515/hukin-2017-0062
|View full text |Cite
|
Sign up to set email alerts
|

Home Advantage in Judo: Analysis by the Combat Phase, Penalties and the Type of Attack

Abstract: Previous studies indicate positive home advantage in judo; however, the factors that influence home advantage have yet to be fully explored. This study investigated the potential differences in technical-tactical variables between home and visiting athletes. A total of 1411 video recorded matches were analyzed (123 home, 1288 away) from 36 international judo competitions contested in 2011-12. The matches were analyzed by the following criteria: combat phases (approach, gripping, attack, defense, groundwork and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 37 publications
0
33
0
Order By: Relevance
“…These findings highlight that judo athletes demonstrated higher phobic and interpersonal anxieties than other modalities. Recent judo rules changes have reduced male combat time to 4 minutes and moments of low-intensity combat time during the approach and gripping time before the attack (Miarka et al, 2016;Brito et al, 2017). A recent study has shown blood lactate rates associated with a protective role against fatigue toward frontal cortex and defined worse performances in backward memory capacity by conditioning strategic ability of the athletes (Coco et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…These findings highlight that judo athletes demonstrated higher phobic and interpersonal anxieties than other modalities. Recent judo rules changes have reduced male combat time to 4 minutes and moments of low-intensity combat time during the approach and gripping time before the attack (Miarka et al, 2016;Brito et al, 2017). A recent study has shown blood lactate rates associated with a protective role against fatigue toward frontal cortex and defined worse performances in backward memory capacity by conditioning strategic ability of the athletes (Coco et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Notational analysis in judo focuses on identifying movement arrangements, often denoted to as "performance indicators", in the competitive situation (Brito et al, 2017). Stanković, Cuk, Milošević, & Stamenković (2015) examined the course of the judo fight at the 2011 World Championship, and diverse motor actions in a total of 959 situations.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the evolution of CB values over time,it should be noted that in men's league seems to remain more stable while in the female league shows a higher variability. As it happens with other sports, the professionalization process has not been so generalized in female teams with respect to the professionalization process of male teams (Brito, Miarka, de Durana, & Fukuda, 2017). For this reason, in the female competitions, there are some teams with many resources competing against others with very different potential in the same league.…”
Section: Discussionmentioning
confidence: 99%